A Laboratory Perspective on the Gutenberg‐Richter and Characteristic Earthquake Models. Issue 8 (2nd August 2021) - Korkolis, Evangelos; Niemeijer, André R.; Paulssen, Hanneke; Trampert, Jeannot
Abstract: Probabilistic seismic hazard analysis (PSHA) is the standard method used for designing earthquake‐resistant infrastructure. In recent years, several unexpected and destructive earthquakes have sparked criticism of the PSHA methodology. The seismological part of the problem is the true frequency‐magnitude distribution of regional seismicity. Two major models exist, the Gutenberg‐Richter (G‐R) and the Characteristic Earthquake (CE) model, but it is difficult to choose between them. That is because the instrumental, historical, and paleoseimological data available are limited in many regions of interest. Here, we demonstrate how a friction experiment on aggregates of glass beads can produce both regular (CE equivalent) and irregular (G‐R equivalent) stick‐slip. Using a new rotary shear apparatus we produced and analyzed large catalogs of acoustic emission (AE) events related to stick‐slip. The distributions of AE sizes, interevent times, and interevent distances were found to be sensitive to particle size and the applied normal stress, and, to a lesser degree, the stiffness of the loading apparatus. More importantly, the system spontaneously switched behavior for short periods of time. In the context of PSHA, if faults are able to switch behavior as our experimental system does, then justifying the choice of either the CE or the G‐R model is impossible based on existing observations. Key Points: A frictional interface can produce both characteristic and power‐law distributed instabilities in the laboratory The system can alternate between the two regimes on the fly If these characteristics are applicable to natural faults, then seismic hazard analysis must take them into account